Management of Eruption Cyst: A Case Report - Syahrir, Syakriani (Hasanuddin University, 2022)
Objective: This study reviews eruption cysts in children and their management related to dental and oral health. It also presents a case report of a 6-year-old boy diagnosed with an eruption cyst on tooth 21.Method: Surgical exposure was performed under local anesthesia, exposing the tooth's crown, removing the remaining root 62, and applying pressure packs for 10 minutes to stop the bleeding.Result: The tooth showed a regular eruption pattern following the removal of the cystic lesion. Therefore, the patient was kept on regular recall. After one month, the tooth erupted in the oral cavity.Conclusion: Surgical intervention is often considered in symptomatic cases where the erupting cyst is painful, bleeding, or infectious, whereas no treatment is required in asymptomatic patients. So, it is crucial to have sound knowledge amongst clinicians regarding eruption cysts to provide proper treatment and reassure the apprehensive parents regarding this lesion.